Unraveling the role of STAT3 in Cancer Cachexia: pathogenic mechanisms and therapeutic opportunities - Lv, Xinyi; Ding, Shengguang (Frontiers in Endocrinology, 2025)
Cancer cachexia is a complex, multifactorial syndrome characterized by severe weight loss, muscle wasting, and systemic inflammation, significantly contributing to cancer-related morbidity and mortality. Signal transducer and activator of transcription 3 (STAT3) has emerged as a central mediator in the pathogenesis of this multifactorial condition. STAT3 regulates a broad range of cellular processes including inflammation, proteolysis, and mitochondrial dysfunction across multiple tissues, particularly skeletal muscle and adipose tissue. Persistent activation of STAT3 in response to tumor-derived and host-derived cytokines drives catabolic signaling cascades, disrupts anabolic pathways, and impairs energy homeostasis. Recent studies have illuminated the cross-talk between STAT3 and other signaling pathways that exacerbate cachexia-related metabolic imbalances. These findings position STAT3 not only as a critical mediator of cachexia progression but also as a promising therapeutic target. Pharmacological inhibition of STAT3 signaling has demonstrated efficacy in preclinical models, offering potential avenues for clinical intervention. This review provides a comprehensive overview of the molecular mechanisms by which STAT3 contributes to cancer cachexia and discusses emerging therapeutic strategies aimed at modulating STAT3 activity to mitigate the progression of this debilitating syndrome.